AN ANALYSIS of DEVELOPMENTS and CHALLENGES CONFRONTING PERSONNEL MANAGEMENT PRACTICE in NIGERIA - Ugoh, Samuel Chuks; Isinkaye, Kehinde; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2024)
This paper explores factors that aided the development of personnel management practices, as well as the challenges confronting the profession in Nigeria. The study made efforts to identify factors such as how industrial revolutions impacted both the industrialized and emerging countries. The study found that despite the fact personnel management practices has passed through several challenges, the challenges can be overcome. The study concluded that with appropriate human resources development, free from political interference in public service, personnel management as a discipline in Nigeria will go from strength to strength.